ESG Integration in SOE Directors' Duties: Comparing Indonesian and Malaysian Corporate Law - Alia Imron (Yayasan Cahaya Generasi Positif, 2026)
This article comparatively analyzes the integration of Environmental, Social, and Governance (ESG) mandates into the fiduciary duties of State-Owned Enterprise (SOE) directors in Indonesia and Government-Linked Companies (GLC) in Malaysia. Utilizing a normative doctrinal approach, this study addresses the systemic tension between ESG transition risks and directors' personal liability. In Indonesia, the rigid state finance doctrine often criminalizes SOE business losses, creating a chilling effect on sustainable investments. Conversely, Malaysia treats GLCs as private entities, evaluating failures through civil mechanisms unless decisions are